PERANCANGAN SISTEM MODUL REGISTRASI PADA SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (STUDI KASUS : RUMAH SAKIT UNIVERSITAS MATARAM) - Askit, Baiq Ratna; Widiartha, Ida Bagus Ketut; Rosika, Herliana (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2025)
This paper presents the design and evaluation of a user-centered registration module for a hospital information system, implemented with a microservices architecture to enable independent development and seamless integration of registration, scheduling, and payment services. A prototype was assessed with 50 participants using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The prototype achieved a SUS score of 78.9, indicating good usability. UEQ results showed excellent ratings in attractiveness, efficiency, stimulation, and novelty, while clarity and dependability scored good, revealing opportunities to improve navigation and instructional messaging. The modular microservices approach enhances scalability, maintainability, and performance. Future work will incorporate load testing, integration testing, and accessibility evaluations to further optimize system robustness and user satisfaction.